Updates in the Management of Retinoblastoma - M. Ashwin Reddy, Shabana Chaudhry, Mandeep S. Sagoo (Pakistan Journal of Ophthalmology, 2014)
Retinoblastoma is the commonest childhood intraocular malignant tumour, with an approximate incidence of 1 in 15,000–20,000 live births worldwide. Advances in treatment over the last quarter century have led to a survival rate that is over 90% in developed countries1 . While paradigm shifts have occurred in conservative treatment, enucleation (removal of the eye) remains the mainstay for treatment for advanced disease. With improved survival rates, there has been an impetus to treat retinoblastoma without removal of the eye and to preserve vision. Previously external beam radiotherapy (EBR) was extensively used to avoid enucleation. However well recognised side effects such as second cancers in the field of radiation, particularly if given in the first year of life, have limited its use to salvage treatment in order to avoid enucleation. 2